Oral Prevotella Species and Their Connection to Events of Clinical Relevance in Gastrointestinal and Respiratory Tracts - Könönen, Eija; Gursoy, Ulvi K. (Frontiers in Microbiology, 2022)
Prevotella is recognized as one of the core anaerobic genera in the oral microbiome. In addition, members of this genus belong to microbial communities of the gastrointestinal and respiratory tracts. Several novel Prevotella species, most of them of oral origin, have been described, but limited knowledge is still available of their clinical relevance. P. melaninogenica is among the anaerobic commensals on oral mucosae from early months of life onwards, and other early-colonizing Prevotella species in the oral cavity include P. nigrescens and P. pallens. Oral Prevotella species get constant access to the gastrointestinal tract via saliva swallowing and to lower airways via microaspiration. At these extra-oral sites, they play a role as commensals but also as potentially harmful agents on mucosal surfaces. The aim of this narrative review is to give an updated overview on the involvement of oral Prevotella species in gastrointestinal and respiratory health and disease.